Generator Pohon Untuk Grammar Berbasis Algoritma Couke Younger Kasami - Wijanarto Wijanarto; Ajib Susanto (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2016)
Syntactic analysis is a series of processes in order to validate a string that is received by a language. In this section it is often difficult to be explained properly, especially when making the rules up into a tree decline valid received by language. This study aims to produce an application that can generate information in the form of image files visual and textual representations of trees from the strings of the received language, a decrease in the rules of grammar, as well as the basic code of the image file that can be compiled and customization of its own. The algorithm chosen is CYK algorithm (Cocke Younger Kasami) for parsing the context free grammar (CFG) in the form of Chomsky Normal Form (CNF). CYK algorithm is very easy to understand and implement, therefore, appropriate given the decline in the teaching of automata to understand the rules to produce a valid tree of the input string. In the study of automata, understanding the process of reduction in the rules to be a tree (parse tree) is important to be taught well